An Effective Option for the Repair of Facial Defects: V-Y Advancement Flaps and Modifications - Derebaşınlıoğlu, Handan; Yilmaz, Sarper; Ipek Uzunoglu, Kadriye (ENT Updates, 2020)
Objective: V-Y advancement flaps are pliable local flaps that can be used in nearly every part of the body with relatively minimal technical difficulty. These flaps provide the best color and quality match, especially in the facial region. With effective planning, donor site morbidity can be acceptable, even on the face. Methods: The results of 38 patients who underwent 53 V-Y advancement flap facial reconstructions were analyzed retrospectively. The defects were evaluated according to their anatomical region, etiology, postoperative complications, and final aesthetic results. Results: V-Y advancement flaps were used for defects that were either not amenable to primary repair or had a high risk of cosmetic distortion. The defects were located in the cheek (9 patients), nasolabial fold (7 patients), nose (6 patients), forehead (5 patients), preauricular area (3 patients), infraorbital region (3 patients), lower lip (1 patients), gingivobuccal sulcus (2 patients), and medial canthal region (2 patients). In 32 patients, the primary pathology was malignant tumor (22 basal cell carcinomas, 9 epidermoid carcinomas, 1 malignant eccrine poroma). Etiologies of the other patients’ defects were benign tumors (n=2), traumatic wounds (n=2), and contractures (n=2). Conclusions: Despite the widespread use of V-Y flaps in surgical practice, the technique continues to demonstrate additional advantages, particularly in facial reconstruction. They are not only applicable for medium and small defects, but can be used for all defects with sufficient surrounding tissue. They enable various modifications and the elevation of multiple flaps.